Treatment persistence to tolvaptan in patients with autosomal dominant polycystic kidney disease: a secondary use of data analysis of patients in the IMADJIN® dataset - Mark Thomas (BMC, 2021)
Abstract Background Tolvaptan is the only available disease-modifying treatment for autosomal dominant polycystic kidney disease (ADPKD). Prior to October 2020 access to tolvaptan in Australia was restricted by a controlled monitoring and distribution program called IMADJIN®. Focusing on hepatic safety, the IMADJIN® program collected real-world data on patients with ADPKD. A retrospective, secondary data analysis of the IMADJIN® dataset was undertaken to determine the time to all-cause discontinuation of tolvaptan in Australia. Methods Demographic and treatment data from 17 September 2018 to 30 September 2020 were extracted from the IMADJIN® dataset. Treatment persistence was analyzed using Kaplan-Meier methods, and Cox’s proportional hazard models were used to analyze differences in treatment persistence by age, sex and location. Results Four hundred seventy-nine patients with ADPKD were included in the analysis. After a median follow-up of 12.0 months (95% confidence interval [CI] 2.6, 23.4), the Kaplan-Meier estimation of 12-month persistence was 76.7% (95% CI 72.2, 80.5%). 114 (23.8%) patients discontinued treatment; sex, state, and remoteness did not significantly affect treatment persistence. Patients in the youngest tertile were more likely to discontinue compared to older ages (p = 0.049). Reasons for discontinuation included: aquaretic tolerability (4.2%), hepatic adverse events (abnormal liver function tests) (2.1%), disease progression (1.5%), and acute kidney injury (0.2%). Patients with a lack of aquaretic tolerance had shorter time to discontinuation. Hepatic toxicity events were initially observed 3 months after tolvaptan initiation and were less prevalent over time. Conclusions Persistence to tolvaptan in the real-world IMADJIN® dataset was 76%. Discontinuation due to hepatic events was low. Prescribers should take extra care when initiating treatment in younger patients as they are more likely to discontinue tolvaptan compared to older individuals. Nevertheless, the precise reason for this observation remains to be elucidated.